PENGARUH KOMPENSASI, KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN PADA RUMAH MAKAN (WARALABA) GAMA RESTO DAN STEAK GERAI PURWOKERTO - Diana Rahmawati; Sudarmi Sudarmi (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2006)
The aims of this research are: first, to examine the effect of compensation, leadership, and job environment on employees job performance. Second, to examine which variable has the greatlest effect on employees job performance at Rumah Makan Gama Gerai Purwokerto. There are two main findings: first, compensation, leadership, and job environment have a significant effect on employees job performance. This was proved through the value of computed –F (32,2626) > Ftable (2.7694) and the value of computed –t of compensation variable (tx1) 42423,, leadership variable (tx2) 2.6262, in the other word tx1, tx2, tx3 are greater than ttable. So the first hypothesis was supported. Second, the elasticity test showed that value of compensation (E1 ) was 0.3803; elasticity of leadership (E2) was 0.2315 and elasticity of job environment (E3) was 0.2673. So, the variable that has the greatest effect on employees job performance was compensation variable. In the other word the compensation has been suitable with employees want and it will increase their job performance. As implication, Rumah Makan Gama Gerai Purwokerto has to pay more attention and try to increase employees job performance by having evaluation on the three variable. It must be done as whether in total or in partial they have significant effect on employees job performance.